Studi Tentang Kitab Sahih Al-Bukhari: A Study on the Sahih al-Bukhari - Pujiono Pujiono (Fenomena, 2002)
The Sahih al-Bukhari is widely regarded as the most authentic book after the Qur’an, yet it has faced serious allegations from certain Western and Muslim scholars that it contains weak or fabricated hadiths due to an alleged lack of matan criticism. This study aims to examine the methodological rigour of Imam al-Bukhari in compiling his Sahih, with particular focus on his stringent conditions for sanad continuity and his attention to matan authenticity. Using a qualitative library research approach and the al-jarh wa al-ta'dīl method, this research analyses both the sanad and matan of disputed hadiths within the book. The findings reveal that al-Bukhari applied uniquely rigorous criteria, including verified physical encounter between transmitters, moral integrity, and scholarly excellence, which exceeded those of many contemporaries. Furthermore, contested hadiths—such as the one about the end of a century and dipping flies into drinks—are shown to be authentic when properly understood or supported by modern medical science. The study concludes that criticisms of Sahih al-Bukhari are largely unfounded and recommends that hadith scholars exercise greater caution and intellectual rigour before questioning canonical sources. Kitab Sahih al-Bukhari dikenal sebagai kitab paling otentik setelah al-Qur’an, namun tidak luput dari tuduhan sebagian sarjana Barat dan Muslim yang menyatakan adanya hadis lemah atau palsu karena dianggap kurang menggunakan kritik matan. Penelitian ini bertujuan mengkaji metodologi Imam al-Bukhari dalam menyusun kitab sahihnya, dengan fokus pada ketatnya persyaratan sanad dan perhatiannya terhadap matan. Menggunakan pendekatan kualitatif pustaka serta metode al-jarh wa al-ta'dīl, penelitian ini menganalisis sanad dan matan hadis-hadis yang diperselisihkan. Hasilnya menunjukkan bahwa al-Bukhari menerapkan kriteria unik dan sangat ketat, seperti keharusan pertemuan fisik antar perawi, integritas moral, dan keunggulan keilmuan. Hadis-hadis yang dikritik—misalnya tentang habisnya seratus tahun dan mencelupkan lalat ke minuman—terbukti sahih setelah dipahami secara kontekstual atau didukung temuan medis modern. Kesimpulannya, kritik terhadap Sahih al-Bukhari sebagian besar tidak berdasar. Penelitian ini merekomendasikan agar pengkaji hadis lebih berhati-hati dan objektif sebelum mempertanyakan sumber kanonik kedua Islam tersebut.